Value of an Encounter from an Ethical Perspective - Najder-Stefaniak, Krystyna (ETHICS IN PROGRESS, 2014)
This article investigates the relationship between the possibilities of actualizing our encounters and the openness of human space. It describes various types of encounters and shows the correlations between the perception of difference and the inclination to contravene certain encounters. The effects of encounters based on antagonistic, complementary, dialectic, and synergistic thinking are explored in a way that helps to better understand the aims and consequences of encounters actualized in diverse frameworks of dialogue. Further, the impact of paradigms of reasoning on how the value of meetings is understood is described. The results of the modern perception of relationships in the subject-object scheme and in the ecosystem paradigm are presented. The latter allows for recognition that encounters can facilitate creative activity by expanding human space.